Improvement of oxygen flux through perovskite membranes using a coating of ultra-divided particles. (15th December 2016) - Guironnet, L.; Geffroy, P.-M.; Richet, N.; Chartier, T.
Abstract: In the last decades, numerous mixed ionic and electronic conducting materials with a perovskite structure have been investigated for their potential applications as membrane materials for oxygen separation applications. This work shows that significant improvement of electrochemical properties of two perovskite materials, La0.6 Sr0.4 Fe0.8 Co0.2 O3-δ (LSFCo6482 ) and La0.5 Sr0.5 Fe0.7 Ga0.3 O3-δ (LSFG5573 ) is obtained using ultra-divided particles perovskite coating. This coating is obtained by dip-coating thanks to a derived sol-gel synthesis route. The ultra-divided particles have a grain size distribution from 300 to 500 nm. The oxygen flux measured using a specific setup shows that the oxygen surface exchange kinetics and bulk diffusion coefficient depend on the microstructure and the chemical composition of the coating material. The relation established between chemical formulation, microstructure, and oxygen flux were used to design optimized membranes. Highlights: Improvement of the oxygen semi-permeation performances. Increasing the kinetic surface exchanges by a coating of ultra-divided particles. Dependence of nature and microstructure of membrane surfaces on the oxygen flux. Development of optimal design from La0.5 Sr0.5 Fe0.7 Ga0.3 O3−δ / La0.6 Sr0.4 Fe0.8 Ga0.2 O3−δ perovskite membranes. Identification of rate determining step evolution in relation with the membrane design.